PERBEDAAN TINGKAT KENYAMANAN PASIEN POST SECTIO CAESAREA ANTARA METODE ENHANCED RECOVERY AFTER CAESAREAN SURGERY (ERACS) DAN NON-ERACS DI RUMAH SAKIT SWASTA KOTA JAMBI - Susi Erika Br. Sembiring; Silvia Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Background: The increasing rate of cesarean section deliveries has increased the need for effective postoperative recovery methods. Enhanced Recovery After Caesarean Surgery (ERACS) is an evidence-based protocol designed to accelerate recovery through pain management, early mobilization, and adequate rest. Objective: To analyze differences in comfort levels between post-cesarean patients managed using ERACS and conventional (non-ERACS) protocols. Methods: This comparative analytic study employed a cross-sectional design involving 60 respondents selected through consecutive sampling. Patient comfort was assessed using pain intensity (Numeric Rating Scale), early mobilization, and resting ability. Data were analyzed using the Mann–Whitney test. Results: No statistically significant differences were found between ERACS and non-ERACS groups regarding pain intensity (p=0.106), early mobilization (p=0.535), resting ability (p=0.132), or overall comfort level (p=0.136). Nevertheless, the ERACS group demonstrated a higher mean rank of comfort than the non-ERACS group. Conclusion: ERACS did not significantly improve patient comfort compared with conventional postoperative care. However, it showed a tendency toward better recovery outcomes and remains a promising evidence-based strategy in post-cesarean care.